Pengukuran Kinerja Rantai Pasok pada Industri Tahu Cibuntu dengan Model Green Supply Chain Operation Reference (GSCOR) (Studi Kasus : Industri Tahu Cibuntu GS Dabeda) - Raden Wally Hafidzh Gurnida; M Dzikron (Bandung Conference Series: Industrial Engineering Science, 2023)
Abstract. The Cibuntu tofu industry is a research site located in Babakan Ciparay Village, Bandung Regency which is an association of Micro, Small and Medium Enterprises (MSMEs) that produce tofu. Cibuntu Tofu Industry has about 16 small-scale to industrial-scale craftsmen in the village. Four entities play a role in the tofu factory supply chain network: suppliers, tofu production houses, retailers, and consumers. Suppliers have two categories involved in this supply chain: soybean suppliers, which provide the main raw materials for tofu production, and firewood providers, which provide fuel for cooking. The two suppliers will talk about the supply of raw materials to the factory after reviewing the demand of tofu manufacturers. Soybean suppliers receive their products from a variety of different sources with firewood providers. Performance design is carried out using the GreenSCOR model, by weighting performance indicators using the AHP method using Expert Choice software. Based on the results of the assessment carried out, the overall performance value of the green supply chain of the Cibuntu tofu industry is in the Good category. However, the company must further improve some performance indicators that are still considered unsatisfactory. The results of the performance indicator assessment there are 12 KPIs that are still below the target, where improvements must be made in order to improve the company's performance by providing recommendations for improvements to performance indicators that are still below the assessment standard. Abstrak. Industri tahu Cibuntu menjadi tempat penelitian yang terletak di Kelurahan Babakan Ciparay, Kabupaten Bandung yang merupakan suatu perkumpulan Usaha Mikro, Kecil dan Menengah (UMKM) yang memproduksi tahu. Industri Tahu Cibuntu memiliki sekitar 16 pengrajin skala kecil hingga skala industri di desa tersebut. Empat entitas berperan dalam jaringan rantai pasokan pabrik tahu: pemasok, rumah produksi tahu, pengecer, dan konsumen. Pemasok memiliki dua kategori yang terlibat dalam rantai pasokan ini: pemasok kedelai, yang menyediakan bahan baku utama untuk produksi tahu, dan penyedia kayu bakar, yang menyediakan bahan bakar untuk memasak. Kedua pemasok akan membicarakan tentang pasokan bahan baku ke pabrik setelah menelaah permintaan produsen tahu. Pemasok kedelai menerima produknya dari berbagai sumber yang berbeda dengan penyedia kayu bakarPerancangan kinerja dilakukan menggunakan model GreenSCOR, dengan pembobotan terhadap indikator kinerja menggunakan metode AHP yang menggunakan software Expert Choice. Berdasarkan hasil penilaian yang dilakukan, nilai kinerja keseluruhan green supply chain industri tahu Cibuntu berada pada kategori Good. Namun, perusahaan harus lebih meningkatkan kembali beberapa indikator kinerja yang dinilai masih tidak memuaskan. Hasil penilaian indikator kinerja terdapat 12 KPI yang masih dibawah target, dimana harus dilakukannya perbaikan agar dapat meningkatkan kinerja perusahaan dengan diberikan rekomendasi perbaikan pada indikator kinerja yang masih dibawah standar penilaian